Answer:
29° ; 61°
Step-by-step explanation:
Let one angle = x°
Other angle = (x + 32)°
x + x + 32 = 90 {given they are complementary}
2x + 32 = 90
2x = 90 -32
2x = 58
x = 58/2
x = 29
One angle = 29°
Other angle = 29 + 32 = 61°
Answer:
No. Remember, a right angle must have a 90 degree angle. We can find the lengths with the Pythagorean Theorem.
Step-by-step explanation:
Given the length 7, 10, and 12, we can assume that 12 is the hypotenuse (it is the longest length).
- we can use 7 and 10 interchangeably.
Fill in the equation,
where c = 12, and a or b = 7 or 10.
To indicate if the given lengths would form a right angle, we can only input 7 or 10, not both.
Therefore, or
==> 49 + b^2 = 144 ==> <u>b= </u><u> ==> </u><u>9.746</u>
b= 9.7, not 10.
==> 100 + b^2 = 144 ==> <u>b = </u><u> ==> </u><u>6.633 </u>
b= 6.6, not 7.
Therefore, the lengths 7, 10, and 12, does NOT make a right triangle.
Hope this helps!
Answer:
each jewel was 3 $
Step-by-step explanation:
divide 108.00/36= 3
The standard form for the equation of a circle is :
<span><span><span> (x−h)^</span>2</span>+<span><span>(y−k)^</span>2</span>=<span>r2</span></span><span> ----------- EQ(1)
</span><span> where </span><span>handk</span><span> are the </span><span>x and y</span><span> coordinates of the center of the circle and </span>r<span> is the radius.
</span> The center of the circle is the midpoint of the diameter.
So the midpoint of the diameter with endpoints at (−10,1)and(−8,5) is :
((−10+(−8))/2,(1+5)/2)=(−9,3)
So the point (−9,3) is the center of the circle.
Now, use the distance formula to find the radius of the circle:
r^2=(−10−(−9))^2+(1−3)^2=1+4=5
⇒r=√5
Subtituting h=−9, k=3 and r=√5 into EQ(1) gives :
(x+9)^2+(y−3)^2=5